Healthy living education on the application of good and correct handwashing and toothbrushing techniques - Dewi Nurhanifah; Saida Kharitilpa (Edukasi Ilmiah Indonesia, 2025)
Clean and healthy living habits are an important foundation in preventing various diseases, especially those transmitted through bacteria, viruses, or germs. Good and correct handwashing and toothbrushing techniques are often considered simple, but their understanding and application in society is still not optimal. This program aims to increase public awareness and knowledge about the importance of washing hands and brushing teeth with the correct method as part of disease prevention efforts. Through an educational approach, the program provides hands-on training and practical demonstrations to the community, especially children and adolescents, on steps to wash hands with soap and brushing techniques that are in accordance with health standards. In addition, interactive counseling was held equipped with visual media and educational games to attract participants. The results of the program showed an increase in participants' understanding of the importance of personal hygiene as well as their ability to practice the techniques taught. This is expected to reduce the risk of infections, especially gastrointestinal diseases, and cavities, as well as build sustainable healthy living habits. This program has a positive impact in supporting the creation of a healthier and more productive society